Symptomatic Meckel's diverticulum in an adult: A case report (International Seven Journal of Health Research, 2024)
Introduction: Meckel's diverticulum (MD) is a true intestinal diverticulum. It originates from failure in the obliteration and absorption of the omphalomesenteric duct during the first trimester of fetal life and affects 2% to 4% of the general population. MD can have its symptomatic or asymptomatic form. The appearance of symptoms suggests complications. The diagnosis depends on the occurrence of complications and is fundamentally based on imaging tests. The definitive treatment of MD is surgical, and the real controversy surrounding MD concerns the option of treating the silent disease with prophylactic resection when discovered during surgery. Objective: To demonstrate the importance of evaluating Meckel's diverticulum, both symptomatic and asymptomatic, as well as the difficulty of its diagnosis, to make a better choice of treatment. Methods: From a medical case that occurred at the Santa Casa da Misericórdia de Presidente Prudente, and its medical records, information was collected to carry out this report. Results: MD is rare and usually asymptomatic in adults, where the definitive treatment is surgical, with absolute indication in symptomatic patients. In asymptomatic patients, surgical treatment is controversial considering the potential for complications versus the risk of the surgical procedure. Conclusion: MD, when symptomatic, is most often associated with complications. It is essential that each case of Meckel's diverticulum be evaluated individually, considering variables such as gender, age (complications are more frequent in children and young men), anesthetic risk, and diverticulum characteristics for a better prognosis and better choice of treatment.